EFFECT OF SOME AGRICULTURAL PRACTICES ON IMPROVING SALTS ‎AFFECTED SANDY SOIL PRODUCTIVITY.‎ - Diia Boulos; Hoda Elia (Arab Universities Journal of Agricultural Sciences, 2019)
A field experiment was conducted on sandy soil at Ismailia Governorate. The aim of the present study is to improve the productivity of salts affected sandy soil by treat it with different rates of bentonite, chicken manure and their combination. Soil application rates were bentonite (1, 2.5 and 5 %), chicken manure (5, 10 and 15 ton/fed) and their combination (2.5% bentonite with each of 5, 10 and 15 ton /fed chicken manure) were mixed in the upper soil layer (0-15 cm soil depth) and their effects on some soil physical properties and crop productivity of fennel plant (Foeniculum Vulgare Mill.) were investigated during the winter season of 2018. The results revealed that, all studied treatments were significantly decreased of soil bulk density compare to control. The applications of bentonite 1, 2.5 and 5% lead to, reduction of the value of soil bulk density by 4.17, 5.95 and 10.71%. In addition, the applications of chicken manure 5, 10 and 15 ton/fed, lead to reduction of the value of soil bulk density by 8.93, 11.31 and 14.88 %. Also, application of 2.5% bentonite combined with each of 5, 10 and 15 ton/fed chicken manure, lead to reduction of the value of soil bulk density by 11.31, 15.48 and 17.86% as compared with control, respectively. Data indicated also that there are an increase in the percentages of retained moisture in the soil at all treatments under study. Bentonite and chicken manure individually or combined being higher with increasing the applied rate of bentonite and/or chicken manure. Also the application rates of bentonite 1, 2.5 and 5% lead to, increasing the values of water-holding pores (WHP) with 6.87, 8.05 and 10.55%. In addition, WHP values increased to 9.21, 10.43 and 11.27% with the application of chicken manure 5, 10 and 15 ton/fed. Also, data refer that WHP increased to 12.03, 12.81 and 14.11% by application rate of 2.5% bentonite combined with each of 5, 10 and 15 ton/fed chicken manure, as compared with control, respectively. The values of water infiltration rates (cm/h), were affected by different soil applications and can be arranged in the following ascending order: 2.5% bentonite + 15 ton/fed chicken manure < 5% bentonite < 2.5% bentonite + 10 ton/fed chicken manure < 2.5% bentonite < 15 ton/fed chicken manure < 2.5% bentonite + 5 ton/fed chicken manure < 10 ton/fed chicken manure < 5 ton/fed chicken manure < 1% bentonite < control. The water use efficiency values, affected by different soil application can be arranged in the following descending order: 2.5% bentonite + 15 ton/fed chicken manure > 2.5% bentonite + 10 ton/fed chicken manure > 2.5% bentonite + 5 ton/fed chicken manure > 15 ton/fed chicken manure > 10 ton/fed chicken manure > 5 ton/fed chicken manure > 5% bentonite > 2.5% bentonite > 1% bentonite > control. ‎